Consistency and its role in the poetic structure of the poem "Little Ghayth" by the poet Ahmed Rafiq Al Mahdawi (Journal of Human Sciences, 2025)
This is a reading of the poem "Ghaith Al-Sagheer" by Ahmed Rafiq Al-Mahdawi. The researcher attempts to determine whether this poem is interconnected and coherent within its parts, with each part related to the one before and after it. She analyzes it to reveal the manifestations of coherence in the poem, monitors its mechanisms, and highlights its role in the artistic construction of this poem as a coherent poetic text. This study adopts a modern linguistic approach and examines it according to three levels: the semantic level, the phonetic level, and the syntactic level.• 1. The semantic level addresses the semantic units in the text, identifying the semantic fields to which these units belong, and how they served the poet and created the tone and rhythm that expresses his ideas.• 2. The phonetic level addresses the sounds of language and their function in producing the text and conveying meaning, and demonstrates how they contribute to its coherence and cohesion.3. The structural level, which addresses how vocabulary is formed to compose sentences and phrases in the text, ensuring they are coherent and cohesive, conveying the poet's intent with regularity and coherence, using well-known cohesive mechanisms such as linking, referral, attribution, and solidarity. The research concludes with a conclusion that includes the findings